Anticorruption School: A Solution to Building the Integrity of Judges - Kiki Kristanto; Zico Junius Fernando; Papontee Teeraphan (IJCLS (Indonesian Journal of Criminal Law Studies), 2023)
The anti-corruption school is an essential solution to help build judges' integrity in the era of Industrial Revolution 4.0 and Society 5.0. The era of Industrial Revolution 4.0 and Society 5.0 requires judges to understand and face increasingly complex and diverse legal challenges, including overcoming increasingly sophisticated and well-organized corruption crimes. The research method used is qualitative. The approaches used are the statutory approach, the conceptual approach, the comparative approach, the futuristic approach, and the philosophical approach. The nature of this research is descriptive-prescriptive, and it was analyzed using content analysis. The result of this research is that the anticorruption school model will help strengthen the integrity of judges, promote transparency and accountability, and increase public trust in the judiciary through a comprehensive and integrated approach. The anti-corruption school model could be an effective solution for helping judges face the challenges of the Industrial Revolution 4.0 and Society 5.0. The Anticorruption School is the best model for creating judges' integrity. Judges can acquire the knowledge, skills, and attitudes through structured and systematic education and training to avoid corrupt practices and maintain their integrity as law enforcers.